NAADP receptors - Galione, A (Cold Spring Harbor Laboratory Press, 2019)
Of the established Ca2+-mobilizing messengers, NAADP is arguably the most tantalizing. It is the most potent, often efficacious at low nanomolar concentrations, and its receptors undergo dramatic desensitization. Recent studies have identified a new class of calcium-release channel, the two-pore channels (TPCs), as the likely targets for NAADP regulation, even though the effect may be indirect. These channels localized at endolysosomes, where they mediate local Ca2+ release, and have highlighted a new role of acidic organelles as targets for messenger-evoked Ca2+ mobilization. Three distinct roles of TPCs have been identified. The first is to effect local Ca2+ release that may play a role in endolysosomal function including vesicular fusion and trafficking. The second is to trigger global calcium release by recruiting Ca2+-induced Ca2+-release (CICR) channels at lysosomal-endoplasmic reticulum (ER) junctions. The third is to regulate plasma membrane excitability by the targeting of Ca2+ release from appropriately positioned subplasma membrane stores to regulate plasma membrane Ca2+-activated channels. In this review, I discuss the role of nicotinic acid adenine nucleotide diphosphate (NAADP)-mediated Ca2+ release from endolysosomal stores as a widespread trigger for intracellular calcium signaling mechanisms, and how studies of TPCs are beginning to enhance our understanding of the central role of lysosomes in Ca2+ signaling.